Improved Vertical Jump After Jumping Rope Practice for Volleyball Extracurricular Players at SMA 1 Arosbaya - Komar Uzzaman; Khoirul Anwar; Heni Yuli Handayani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This research is based on discussions with a senior Physical Education trainer (teacher) at SMAN 1 AROSBAYA, Bangkalan Regency, one of the subjects the students really like. I really like volleyball sports materials. Teachers in the field of Physical Education, Health and Recreation at SMAN 1 AROSBAYA apply that when teaching students, almost all students are happy and understand the material. The purpose of this study was to determine the effect of jumping rope training on the vertical jump of volleyball athletes in the extracurricular activities of SMAN 1 Arosbaya. Based on the frequency distribution in table 4.2, the results of the pretest and posttest of Jumping Rope Exercises for Volleyball Extracurricular Vertical Jump at SMA 1 Arosbaya, Bangkalan Regency, namely based on the output above, the mean value of the I/Pre Test test was 228.27 cm while for Test II/posttest it was 229 ,93. So it can be concluded that the average training acquisition has a different average. Based on the output that has been tested, that the significance value is 0.000 > 0.05, there is a significant change in the results of the Jump Rope Exercise experiment on Volleyball Extracurricular Jump at SMA 1 Arosbaya, Bangkalan Regency.